“Common errors in Vietnamese-English translation made by English translator trainees at Nui Phao Mining Company Limited”. - Đinh, Thị Hòa (University of Languages and International Studies, 2017)
The study investigated the common errors in Vietnamese-English translation made by English translator trainees working at NPMC. By analyzing Vietnamese-English translations, two main types of translation errors were linguistic errors and translation errors (...)